Welfare Analysis of Households Involved in Involuntary Resettlement in Koto Panjang - Fery Andrianus, Syafruddin Karimi, Melinda Noer, Werry Darta Taifur (Universitas Andalas, 2018)
It has been said that development requires sacrifice. This has been the experience of households living in Koto Panjang, Sumatra, Indonesia. Because of new dam construction, they have had to move to new settlements provided by the government. The displaced community consists of 4868 families from 10 villages. Many problems have arisen due to this removal. This study examines the influence of household participation and compensation on household welfare by using a Structural Equation Model. The sample consisted of 360 household heads from 12 villages in Koto Panjang whose households had been moved. The results show that compensation positively and significantly affected household welfare, while household participation could not be proven to affect household welfare.